DESENTRALISASI FISKAL DAN PERTUMBUHAN EKONOMI Perlukah desentralisasi fiskal diperluas? - Galela, Muhammad Ridhwan (JURNAL INFO ARTHA, 2016)
The needs of comprehensive fiscal decentralization in Indonesia arose after the economic crisis with the aim of maintaining Indonesia. After the crisis passed, some people consider fiscal decentralization led to slow economic growth in the regions. Fiscal decentralization can stimulate economic growth by arguing that the budget allocation for local public goods by local governments will be more in line with the needs of the community because of the information advantage by the local government. Meanwhile, decentralization also poses a risk of constraining economic growth due to inflation of bureaucracy, low economic scale, market fragmentation and corruption. Tests to determine the correlation between economic growth and fiscal decentralization was made by using fiscal decentralization indicators that show the length of fiscal authority delegation, both in terms of expenditure and revenue sides. The studies conducted show different results, some show positive correlation, others indicate negative correlation, and the rest are not correlated. Differences in the results of this study make it difficult for policy-making to increase or decrease the delegation of authority. Regardless of the outcome, the purpose of unificating Indonesia through fiscal decentralization has been reached.